Pengaruh variasi kecepatan putaran spindle frais milling terhadap sifat kekasaran alumunium 6061 - Firmansyah, Mochammad; Wati, Dian Anisa Rokhmah; Pramitasari, Retno Eka; Wijanarko, Nadia Parwaty (Program Studi Teknik Mesin Fakultas Teknik Universitas Pasundan, 2025)
This research aims to determine the roughness level of a 6061 aluminium workpiece by varying the spindle rotation speed in the milling machine. The results of this study are data on surface roughness obtained through variations in spindle rotation speed during milling. This research uses experimental research methods. Methods that aim to test the effect of a variable on other variables or test the causal relationship between one variable and other variables. The results of this study are presented as roughness test results. The test results using spindle rotation n_1 = 410 rpm; n_2 = 570 rpm; n_3 = 660 rpm. The lowest roughness value occurs at spindle rotation n_3 = 660 rpm, producing an average roughness value of 0.697 µm. The highest roughness value occurs at a spindle rotation of n_1 = 410 rpm, yielding an average roughness of 2.164 µm. Testing at 660 rpm yields smoother results than at 570 rpm and 410 rpm.